Métodos numéricos na análise de antenas e estruturas passivas em tecnologia de microfita - Silveira, Eduardo dos Santos (Universidade Federal do Pampa, 2013)
Abstract: In the last decades, with the growth in computational power, it has become possible to solve problems that do not have analytical solutions by the development of numerical methods. In this context, this document aims to present a numerical analysis of wire antennas using the Method of Moments and microstrip passive structures, using the Discrete Mode Matching method. Therefore, two computational tools have been developed using the software Matlab R○. The results with the numerical analyzes were validated using commercial software, verifying the accuracy of the employed methods. Finally, the computational tools that have been built are adaptable to other geometries of antennas or microstrip passive structures and can be used as a basis for the analysis of more complex structures.
Keywords: Electrical engineering; Antennas; Electromagnetism; Numerical methods; Engenharia elétrica; Antenas; Eletromagnetismo; Métodos numéricos; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA::TELECOMUNICACOES::TEORIA ELETROMAGNETICA, MICROONDAS, PROPAGACAO DE ONDAS, ANTENAS